EFFECT OF WASTE POLYETHYLENE TEREPHTHALATE BOTTLE FIBERS ON THE MECHANICAL PROPERTIES OF RECYCLED CONCRETE (Advances in Civil and Architectural Engineering, 2023)
The use of beverage containers, most of which are made of polyethylene terephthalate bottles, results in several problems with regard to sustainability. The purpose of this study was to evaluate and contrast the impact on the mechanical characteristics of concrete caused by the incorporation of polyethylene terephthalate bottle fibres in varying amounts. These fibres were generated by cutting bottles into precise dimensions (width of 5 mm and length of 25 mm), and they were used in various concentrations such as 0,25 %; 0,5 % and 1,0 % by volume of concrete with different amounts of recycled aggregate. To verify the reliability of the outcomes of the experiment, a statistical analysis was performed. According to the results, the concrete that contained 0 % recycled coarse aggregate and varying amounts of plastic fibres had a greater degree of workability compared with concrete that had either 50 % or 100 % recycled coarse aggregate. The comprehensive test findings demonstrated that the addition of polyethylene terephthalate fibres decreased compressive and split tensile strength. The study concluded that certain parameters, such as plastic fibres, curing days, and recycled aggregate, interacted together in a synergistic manner to impact the compressive and splitting tensile strengths of the concrete, with proposed equations for their prediction.